Pengembangan Modul Ajar Berbasis Ekologi pada Materi Teks Eksposisi untuk Meningkatkan Literasi Bahasa Siswa SD: Development of Ecology-Based Teaching Modules on Expository Text Material to Improve Elementary School Students' Language Literacy - Veronika Banjarnahor; Khairil Anshari; Wisman Hadi (ITScience (Information Technology and Science), 2026)
Language literacy is a skill involving reading, listening, comprehending, analyzing, and critically evaluating information, followed by the ability to express that information in written text. Observations at SD Negeri 104212, Patumbak District, Deli Serdang Regency, revealed low student literacy scores (65.27) and an average Indonesian language subject score of only 54.77. Furthermore, the teaching method employed was the lecture method; there were no practical activities or literacy projects, and the teaching materials were inadequate—specifically, the quantity of materials did not match the number of students. The study utilized the Research and Development (R&D) method based on the ADDIE model, comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. Subject matter expert validation yielded a final score of 83% (classified as